Studi Komparasi Pembagian Harta Warisan Menurut Adat Dan Hukum Islam Desa Pace Kecamatan Silo Kabupaten Jember - Abdul Halim (Fakultas Syariah Program studi Hukum Keluarga Islam IAI Al- Qodiri, 2024)
Inheritance is one of the most important world affairs, for Muslims themselves, because matters related to inheritance are one of the obligations that must be carried out as best as possible by Muslims themselves, because this shows faith and piety to Allah and His Messenger. Islam places great importance on the issue of